PRAWNOKARNA OCHRONA CZCI A POSTULATY UCHYLENIA BĄDŹ REWIZJI ART. 212 KODEKSU KARNEGO - Jóźwiak, Piotr (Wydział Prawa i Administracji UAM, 2009)
An attempt is made to answer a question whether legal protection of honour included in article 212 of the Penal Code constitutes a threat to the constitutional freedom of speech. Raising this issue is also justified in the light of the demands to repeal or revise the legal protection of honour and personal dignity provided in criminal law. The recognition by the Constitutional Tribunal of clauses 1 and 2 of article 212 as being in line with the Constitution has not ended the disputes concerning this issue. And yet, a removal of article 212 from the Penal Code as well as its amendment would have to be based on an assumption that honour and good name are values of lower rank than the freedom of speech. Such an approach is unacceptable in the absence of classification criteria of these values. Consequently, any attempt to narrow down criminal responsibility for the tort of defamation seems to be wrong. Finally, the difference between the function of civil law (compensation) and criminal law (repression) does not allow substitution of criminal punishment with measures or remedies available in civil law.
LEGAL PROTECTION OF REPUTATION IN CRIMINAL LAW AND DEMANDS TO REPEAL OR REVISE ARTICLE 212 OF THE PENAL CODE